Absolute synovial polymorphonuclear neutrophil cell count as a biomarker of periprosthetic joint infection. (15th March 2023) - Jandl, Nico M.; Kleiss, Sebastian; Mussawy, Haider; Beil, Frank T.; Hubert, Jan; Rolvien, Tim
Abstract : Aims: The aim of this study was to evaluate the diagnostic accuracy of the absolute synovial polymorphonuclear neutrophil cell (PMN) count for the diagnosis or exclusion of periprosthetic joint infection (PJI) after total hip (THA) or knee arthroplasty (TKA). Methods: In this retrospective cohort study, 147 consecutive patients with acute or chronic complaints following THA and TKA were included. Diagnosis of PJI was established based on the 2018 International Consensus Meeting criteria. A total of 39 patients diagnosed with PJI (32 chronic and seven acute) and 108 patients with aseptic complications were surgically revised. Results: Using receiver operating characteristic curves and calculating the area under the curve (AUC), an optimal synovial cut-off value of 2, 000 PMN/µl was determined (AUC 0.978 (95% confidence interval (CI) 0.946 to 1)). Using this cut-off, sensitivity and specificity of absolute synovial PMN count for PJI were 97.4% (95% CI 91.2 to 100) and 93.5% (95% CI 88.9 to 98.1), respectively. Positive and negative predictive value were 84.4% (95% CI 72.7 to 93.9) and 99.0% (95% CI 96.7 to 100), respectively. Exclusion of 20 patients with acute complications improved specificity to 97.9% (95% CI 94.6 to 100). Different cut-off values for THA (< 3, 600 PMN/µl) and TKA (< 2, 000 PMN/µl) were identified. Absolute synovial PMN count correlated strongly with synovial alpha-defensin (AD) ( r = 0.759; p < 0.001). With a positive AD result, no additional PJI could be identified in any case. Conclusion: Absolute synovial PMN count is a widely available, rapid, cost-effective, and accurate marker in PJI diagnostics, whereas synovial AD appears to be a surrogate parameter of absolute synovial PMN count. Despite limitations in the early postoperative phase, wear, and rheumatic diseases in confirming PJI, an absolute synovial PMN count below 2, 000/µl is highly suitable for ruling out PJI, with specific cut-off values for THA and TKA. Cite this article: Bone Joint J  2023;105-B(4):373–381.